Ответ:
ниже
Объяснение:
[tex]2x^{2} +3x-2=0\\D=3^{2}-4*2*(-2)=9-(-16)=9+16=25\\x_{1} =\frac{-3-\sqrt{25}}{2*2}=\frac{-3-5}{4}=\frac{-8}{4}=-2\\x_{2} =\frac{-3+\sqrt{25}}{2*2}=\frac{-3+5}{4}=\frac{2}{4}=\frac{1}{2} =0.5[/tex]
Ответ: х1 = -2; х2 = 0.5
2x²+3x-2=0
Д=9+4×2×2=25
x¹=3+5/4=2
x²=3-5/4=-1/2
x¹=2,x²=-1/2
поставте будь ласка корону (найкращу відповідь)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
ниже
Объяснение:
[tex]2x^{2} +3x-2=0\\D=3^{2}-4*2*(-2)=9-(-16)=9+16=25\\x_{1} =\frac{-3-\sqrt{25}}{2*2}=\frac{-3-5}{4}=\frac{-8}{4}=-2\\x_{2} =\frac{-3+\sqrt{25}}{2*2}=\frac{-3+5}{4}=\frac{2}{4}=\frac{1}{2} =0.5[/tex]
Ответ: х1 = -2; х2 = 0.5
Verified answer
Ответ:
2x²+3x-2=0
Д=9+4×2×2=25
x¹=3+5/4=2
x²=3-5/4=-1/2
x¹=2,x²=-1/2
поставте будь ласка корону (найкращу відповідь)